EVALUASI KINERJA ALGORITMA PENGALOKASIAN KANAL TRAFIK DI JARINGAN GSM/GPRS - Hardjono, Pudji
Abstract : General Packet Radio Service (GPRS) is a new packet data communication service implemented in Global System for Mobile communications (GSM) network.To introduce this service into existing GSM network, GSM operator has to integrate two new network nodes that are : Serving GPRS Support Node (SGSN)and Gateway GPRS Support Node (GGSN). SGSN responsible for delivery of packet data from and to Mobile Station (MS) within it\'s service area, and GGSN act as interface between GPRS backbone network and external packet data network. While existing GSM equipments in the Base Station Subsystem (BSS) are used for both services. Within a cell, the usage of available traffic channel could be shared for delivering GSM and GPRS services. So it needed a traffic channel allocation algorithm in order to obtain channel utilization in an efficient way. Operator can decide whether some physical channel are permanently dedicated or temporarily dedicated for transferring GPRS data. Evaluation of the channel allocation algorithm with permanent and temporary data channel will be described in this report. Performance measures are obtained by a simulation that yield the value of Grade of Service (GOS) for GSM and Quality of Service for GPRS, as the data load and the number of GPRS channel vary. The simulation result show that for permanent channel data allocation the QOS is higher as the number of data channel increased, while the GOS is lower. For temporary channel data allocation, the QOS and GOS are approximate constant, although the number of data channel increased.